Green Synthesis of Polypogon monspeliensis–Based Silver Nanoparticles and Their Multifunctional Biomedical Potential - Alaa M. Alrudainy; Ahmed Mshari (Academia Open, 2026)
General Background: Green synthesis of silver nanoparticles has gained attention as a sustainable approach to produce bioactive nanomaterials for biomedical use. Specific Background: Polypogon monspeliensis contains diverse phytochemicals that can function as reducing and stabilizing agents in plant-mediated nanoparticle synthesis. Knowledge Gap: Its potential as a green bioresource for fabricating multifunctional silver nanoparticles remains insufficiently explored. Aims: This study aimed to synthesize, characterize, and evaluate the antibacterial, antioxidant, and anticancer activities of P. monspeliensis–derived silver nanoparticles (Pol-AgNPs). Results: Pol-AgNPs were successfully synthesized, exhibiting crystalline, quasi-spherical particles (≈51–69 nm) with notable dose-dependent antibacterial activity, strong DPPH radical scavenging capacity, and selective cytotoxicity against A549 lung cancer cells. Novelty: The work demonstrates the dual functional role of P. monspeliensis extract in nanoparticle synthesis and bioactivity. Implications: Pol-AgNPs represent promising eco-friendly nanomaterials for future biomedical applications.Keywords : Green Synthesis, Polypogon Monspeliensis, Silver Nanoparticles (AgNPs), Antibacterial And Antioxidant Activity, Anticancer NanomaterialsHighlight : Plant extract reduced Ag+ yielding quasi-spherical, crystalline materials sized 51–69 nm. Dose-dependent antibacterial action strongest against Pseudomonas aeruginosa among tested pathogens. High radical scavenging and selective cytotoxicity toward A549 cells with limited normal fibroblast toxicity.